Theoretical Explanation of the Decision to Separate Among Women Seeking Divorce Referred from Family Courts in Jiroft - Majazi Dalfard, Mohammad; Vaziri, Saeed; Fallah, Mohammad Hossein; Barzegar Bafrooei, Kazem (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to theoretically explain the decision to separate among women seeking divorce referred from family courts in Jiroft. Methods and Materials: The present research employed a qualitative approach using grounded theory. The study population included women seeking divorce in Jiroft, selected through purposive sampling. Data were collected through semi-structured interviews with 22 women and continued until theoretical saturation was achieved. Data analysis was conducted using open, axial, and selective coding. Findings: The findings of the study indicated that women's decision to separate is influenced by multiple factors, which can be categorized into three main domains: relational issues, financial and economic problems, and psychological and personality difficulties. Relational issues encompassed a lack of mutual understanding, aggression, and controlling behaviors, while financial problems such as unemployment and financial disputes were also identified as significant factors. Additionally, psychological and personality disorders, infidelity, and interference from the spouse's family were influential factors. The way couples dealt with these issues was predominantly unhealthy, involving withdrawal, aggression, and neglect of each other's needs. Conclusion: The results of this study suggest that women's decision to separate is shaped by multidimensional factors, necessitating special attention from social, economic, and cultural institutions. It is recommended that educational programs be implemented to enhance communication and conflict resolution skills among couples, provide financial and economic support for women at risk of divorce, reduce social stigma associated with divorce, and offer post-divorce counseling services. These measures could contribute to lowering divorce rates and improving the quality of life for divorced women.